Do environmental regulations hamper productivity growth? How accounting for improvements of firms' environmental performance can change the conclusion - Kjetil Telle; Jan Larsson (Statistics Norway, Research Department, 2004)
Many economists maintain that environmental regulations hamper productivity growth. However, recently, an opposing view has gained advocates. Indeed, it has been suggested that the empirically detected inverse relationship between environmental regulations and productivity growth is an almost inevitable consequence of the current methods used to measure productivity - methods that fail to account for improvements in environmental performance. We apply a method that amends this methodological shortcoming of previous empirical studies, and perform a regression analysis of regulatory stringency and a measure of productivity growth that accounts for emission reductions. To credit a firm for emission reductions, we include emissions as inputs when calculating the Malmquist productivity index (EMI); and for the sake of comparison, we also calculate the traditional Malmquist productivity index (MI) where emissions are not included. The regression analysis shows that the sign of the relationship is positive when EMI is employed as measure of productivity growth; but not statistically different from zero when MI is applied. Hence, the present paper provides the first empirical support for the claim that evaluations or recommendations of environmental policies that are based on a traditional measure of total factor productivity can be biased.
Keywords: Q28; D24; Q25; L60; 330; Environmental regulation; Productivity; Malmquist index